RELIGIOUS ATTITUDES, DEMOGRAPHIC VARIABLES, AND PREJUDICE TOWARD SYRIAN REFUGEES IN TURKEY: LOCAL DATA AND INTERNATIONAL DIFFERENCES - Sağır, Zeynep; Paloutzian, Raymond F. (Kilis 7 Aralık Üniversitesi, 2020)
Prejudice against people of ethnic groups different than one’s own can be central to intergroup conflict. A person’s religiousness may function to either facilitate or retard prejudices, depending upon whether the way the religion is held fosters perceiving others as outsiders and in an “us versus them” manner. These considerations raise concerns about increased expression by Turkish citizens of attitudes against the Syrian refugees that fled to Turkey between 2011 and 2019. The present study used quantitative methods to examine prejudice against Syrian war refugees and asylum seekers as related to religious attitudes and demographic variables in 400 Turkish Muslims in rural Eastern Anatolia, making this a unique dataset that adds to the international pool of information about religion and prejudice. Analyses of measures of social distance from others, feelings toward the outgroup, and religious attitudes showed that prejudice decreased as religious attitudes became more positive, and that women’s religious attitudes were more positive than those of men. Participants with lower monthly income had significantly higher religious attitudes and lower social distance scores than those with high income. People studying Engineering, Education, and Arts and Science showed greater prejudice than those studying Theology. The findings help expand our knowledge base of the relation between religion and prejudice, and document differences between the present findings and those of studies of this relationship in other countries and religions.

Etnik gruplardan insanlara karşı olan önyargı kişinin kendisinin gruplar arası çatışmada merkezde bulunabilmesinden farklıdır. Bir kişinin dindarlığı, dinin “biz ve onlar” şeklinde başkalarını yabancı olarak algılamayı teşvik edip etmediğine bağlı olarak önyargıların ortaya çıkmasını kolaylaştırabilir ya da yavaşlatabilir. Bu hususlar, Türkiye Cumhuriyeti vatandaşlarının 2011-2019 yılları arasında Türkiye’ye göçen Suriyelilere yönelik tutumlarda daha fazla ifade edilmesi konusunda endişeler uyandırmaktadır. Bu araştırmada, Doğu Anadolu’da 400 TürkMüslüman’ın dini tutumu ve demografik değişkenlerle ilişkili olarak Suriyeli mülteci ve sığınmacılara yönelik önyargılı tutumlarını incelemek için nicel yöntem kullanılmıştır. Böylelikle, din ve önyargı konusunda uluslararası bilgi havuzuna özgün bir veri seti eklenmiştir. Öteki ile sosyal mesafe, dış gruba yönelik duygular ve dini tutum konusundaki analizler, dini tutumların daha olumlu hale gelmesiyle önyargının azaldığını ve kadınların dini tutumlarının erkeklerden daha olumlu olduğunu göstermiştir. Aylık geliri daha düşük olan katılımcılar, yüksek gelire sahip olanlara göre önemli ölçüde daha yüksek dini tutumlara ve daha düşük sosyal mesafe puanlarına sahiptir. Mühendislik, Eğitim ve Fen-Edebiyat fakültesinde okuyan insanlar, İlahiyat okuyanlardan daha fazla önyargı göstermiştir. Bulgular, din ve önyargı arasındaki ilişkiye dair bilgi tabanımızı genişletmeye yardımcı olmakta ve mevcut bulgular ile diğer ülkelerde ve dinlerde bu ilişkiyle ilgili çalışmaların bulguları arasındaki farklılıkları ortaya koymaktadır.
DİNİ TUTUM, DEMOGRAFİK DEĞİŞKENLER VE TÜRKİYE’DEKİ SURIYELİ MÜLTECİLERE YÖNELİK ÖNYARGI: YEREL VERİLER VE ULUSLARARASI FARKLILIKLAR
Keywords: Religious Studies; Din Araştırmaları